Uptake of colorectal cancer screening: system, provider and individual factors and strategies to improve participation. (November 2009) - Power, Emily; Miles, Anne; von Wagner, Christian; Robb, Katie; Wardle, Jane
Colorectal cancer (CRC) accounts for 9% of all new cancer cases worldwide and affects over 1 million people each year. Screening can reduce the mortality associated with the disease, yet participation rates are suboptimal. Compliers with CRC screening are less deprived; they have higher education than noncompliers and tend to be male, white and married. Likely reasons for nonparticipation encompass several ''modifiable'' factors that could be targeted in interventions aimed at increasing participation rates. Successful intervention strategies include organizational changes, such as increasing access to fecal occult blood test (FOBT) kits, providing reminders to healthcare providers or users about screening opportunities, and educational strategies to improve awareness and attitudes towards CRC screening. Multifactor interventions that target more than one level of the screening process are likely to have larger effects. The biggest challenge for future research will be to reduce inequalities related to socio––economic position and ethnicity in the uptake of screening.